Zirconium mesostructures entrapped in calcium alginate for treating phosphate ion in reject water after sludge dewatering - Yeon, K. H.; Lee, S.; Park, Y. M.; Choi, Y. S.; Lee, S. H. (DESTECH PUBLICATIONS, INC, 2007)
The zirconium mesostructures (ZM), which have a high sorption capacity for phosphate in its original powder form, were molded by calcium alginate to have a bead form for practical application. And the ZM bead was estimated as a potential adsorbent for the phosphate in reject water after sludge clewatering by varying ZM contents in it and its particle size. It was found that more than 99% of phosphate could be removed under optimal conditions using ZM beads. The maximum sorption capacity of ZM beads for the single-existing phosphate in distilled water was estimated to be 56.7 mg/g. Even though the ZM bead had 1.8 times lower phosphate sorption capacity than the equivalent original ZM powder, it still showed 2.2 times higher capacity than the existing anion adsorbent like activated alumina. This study showed that ZM bead could be used as a promising adsorbent for treating the phosphate in the reject water after sludge clewatering.
Keywords: WASTE-WATER; REMOVAL; PHOSPHORUS; ADSORPTION; RECOVERY